A survey on the prevalence of some ectoparasite species infesting sheep and goats in Kalar district, Kurdistan region, Iraq - Sarkawt R. Kakabwa; Omer M. Amin; Noor N. Polus; Nabeel A. Mawlood2 (Zanco Journal of Pure and Applied Sciences, 2021)
Tamed small ruminants such as sheep and goats are deemed important sources of people livelihood in Garmian area including Kalar district. Sustainability and prosperity of livestock resources are vigorously influenced by the heavy infestation of small ruminants with ectoparasites owing to the enormous economic loss caused by them, particularly in under-developed countries including Iraq. Hence, the present survey, carried out from March, 2019 to February, 2020 in Kalar district, intended to investigate the rampancy of external parasites among sheep and goats being reared in the aforementioned district. To meet the requirements of the survey, a total of 1700 sheep and 400 goats were arbitrarily sampled. The overall rate of ectoparasitosis in this study was 53.09%, in that, the infestation rate in goats (95%) was significantly higher than that of sheep (43.23%). Regarding sheep pediculosis, two species of lice; Linognathus (L.) africanus (35.58%), Damalinia (D.) ovis (24.11%), and two species of ticks; Hyalomma (H.) anatolicum (2.94%), Rhipicephalus (R.) turanucus (4.41%), in addition to the nasal bot fly, Oestrus ovis (12%) were identified. On the other hand, two species of lice; D. caprae (80%), L. africanus (30%), and two species of ticks; H. anatolicum (7.5%) and R. turanucus (3.75%) were detected in goats. Co-infections were significantly higher in sheep as compared to goats in this survey. Some of the aforementioned external parasites are known to transmit zoonotic diseases since sheep and goats are reared in close cohabitation with humans. For that reason, sustainable control of ectoparasitosis especially, tick infestations in domestic livestock is compulsory to prevent both economic loss and transmission of some serious diseases.